2009
DOI: 10.1021/ja906911q
|View full text |Cite
|
Sign up to set email alerts
|

Temperature and Concentration Control over Interpenetration in a Metal−Organic Material

Abstract: A pillared framework formed from 4,4'-bipyridine (bipy) and sheets of dinuclear Cd(2) nodes and 1,4-benzenedicarboxylic acid (bdc) linkers can be prepared in both interpenetrated and noninterpenetrated forms by simply varying the temperature or concentration of the reaction. These results demonstrate that higher temperatures and concentrations favor interpenetration over the corresponding noninterpenetrating structure, an observation that could have broad implications for controlling the synthesis of metal-org… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
185
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 375 publications
(188 citation statements)
references
References 26 publications
3
185
0
Order By: Relevance
“…In order to avoid the self-catenation, several strategies have been demonstrated such as liquid-phase epitaxy, 5 template method in synthetic solution, 6 rational design of organic linkers, 7 or modification of the synthetic condition of PCPs. 8 In contrast to this research direction to obtain the larger pore size, a number of studies have demonstrated that entangled frameworks are not quite so bad as once thought, especially thanks to their unique structural dynamics.…”
Section: ç Introductionmentioning
confidence: 99%
“…In order to avoid the self-catenation, several strategies have been demonstrated such as liquid-phase epitaxy, 5 template method in synthetic solution, 6 rational design of organic linkers, 7 or modification of the synthetic condition of PCPs. 8 In contrast to this research direction to obtain the larger pore size, a number of studies have demonstrated that entangled frameworks are not quite so bad as once thought, especially thanks to their unique structural dynamics.…”
Section: ç Introductionmentioning
confidence: 99%
“…Although rapid progress in the construction of MOFs has been made, it is still a considerable challenge to control the final structures, because many factors, such as temperature [9,10], solvent [11,12], metal/ligand ratios [13], pH values [14,15], influence the formation of the final structure. O-donor organic ligands, rigid benzene multicarboxylate ligands have attracted considerable attention due to their various coordination modes (monodentate, bridging, chelating).…”
Section: Discussionmentioning
confidence: 99%
“…The role of temperature in controlling the assembly process may be rationalized, as higher temperatures would naturally be expected to afford more thermodynamically stable and denser crystal forms. [11] The solid-state CD spectra of 1-3 made from R and S enantiomers of L are mirror images of each other, thus indicating their enantiomeric nature. Calculations using PLATON indicate that 39.8, 59.0, and 45.2 % of the total volume of 1-3, respectively, are occupied by solvent molecules.…”
Section: Methodsmentioning
confidence: 98%